Robot-assisted percutaneous pedicle screw fixation in thoracolumbar burst fractures: a comparative study - Peng Liu; Jiang Hu; Wei Zhang; Shu Lin; Yang Yu; Liuyi Tang; Fei Wang (Scientific Reports)
Abstract The optimal treatment for neurologically intact thoracolumbar fractures remains controversial. Percutaneous pedicle screw fixation (PPSF) has been proposed for certain type AO/A3 fractures without neurological deficits; however, achieving satisfactory reduction remains challenging. This study applied robot-assisted PPSF and compared it with free-hand techniques to enhance treatment outcomes. We retrospectively analyzed the medical records of 182 consecutive patients with thoracolumbar burst fractures treated with PPSF, with (n = 88) and without (n = 94) robotic assistance, at our hospital between April 2017 and June 2019. We evaluated surgical time, intraoperative bleeding, radiation dosage, accuracy of screw placement, fractured vertebral height, Cobb’s angle, surgery efficacy (pain relief and limb function), and implant failure to assess the potential advantages of robot-assisted PPSF. Significant differences were observed in surgical time (P < 0.001), intraoperative bleeding (P = 0.017), pedicle screw violation (P < 0.001), fractured vertebral height and Cobb’s angle at one week postoperatively (P = 0.001, P = 0.024) and at twelve months postoperatively (P = 0.001, P = 0.002). However, implant failure (P = 0.587), analgesic effect, and function recovery at one week postoperatively (P = 0.725, P = 0.093) and at twelve months postoperatively (P = 0.232, P = 0.259) were similar in both groups. Robot-assisted PPSF for thoracolumbar burst fractures reduces surgery time, intraoperative bleeding, and improves screw placement accuracy, achieving better reduction compared to the free-hand technique. It also effectively prevents endplate collapse and kyphosis recurrence post-surgery, though short-term functional recovery is similar between both methods. However, due to the limitations of retrospective studies and cohort heterogeneity, further long-term follow-up and prospective studies are needed to validate these findings.